The Voices Who Live in Us - Krog, Antjie (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
My mother writes ... One morning a man who owed my husband a substantial amount of money, pitched up in a rattling, worn-out bakkie. ‘My husband is not here,’ I said. ‘No, it’s okay, Antie, I just brought the uncle a sirpraais.’ And he took some scaffolding down and a white wooden box. ‘Doesn’t she look beautiful, Antie?’ ‘Are there bees in it?’ I ask carefully. ‘Tjok and blok, my antie, tjok and blok. You see, this hive will create three, four other swarms a year and soon the uncle will have a whole bee farming business.’ ‘But bees sting!’ I interrupted. ‘Sting?’ he seemed utterly astonished. ‘These bees do not sting, Antie. These ones are not the small nasty kind of bee, it is the fat striped one. When they know you, they actually fly out of the hive towards you to welcome you...’ We both heard my husband’s bakkie coming up the road and before I could say anything, the money borrower was back in his own bakkie and revving away. My suspicion was correct, the uncle was not pleased about this goldmine dropped in his yard.